Gene Analysis For Chemotherapy Prescription - Молодецька Д. (Едельвейс, 2024)
Development and spread throughout the body, possible mechanisms, and strategies of the cruel “killer”. From Normal to Cancer, development of the tissue the most dangerous types of cancer and possible treatment solutions. Efficiency of the chemotherapy is closely related to possible mutations that are individual for every patient and cannot be predicted based on the statistics of any type of cancer
Keywords: cancer; gene analysis; chemotherapy